2003
DOI: 10.1128/jvi.77.2.1462-1468.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Hamster Viscerotropic Strain of Yellow Fever Virus

Abstract: A hamster viscerotropic strain of yellow fever (YF) virus has been derived after serial passage of strain Asibi through hamsters. The parental Asibi/hamster p0 virus causes a mild and transient viremia in hamsters with no outward, clinical signs of illness. In contrast, the viscerotropic Asibi/hamster p7 virus causes a robust viremia, severe illness, and death in subadult hamsters. The genome of the hamster viscerotropic Asibi/ hamster p7 virus has been sequenced and compared with the parental nonviscerotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
(75 reference statements)
0
51
0
Order By: Relevance
“…The absence of YFV repetition motifs RYF1 and RYF2 (YFVSADM1) and the presence of RYF3, conserved sequence 2 (CS2), 3=UAR, and 3=CYC sequences was observed (8,24). Furthermore, the pentanucleotides 3=CACAG observed in the 3=SL of flaviviruses were absent from strains with the YFVSADM2 deletion.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The absence of YFV repetition motifs RYF1 and RYF2 (YFVSADM1) and the presence of RYF3, conserved sequence 2 (CS2), 3=UAR, and 3=CYC sequences was observed (8,24). Furthermore, the pentanucleotides 3=CACAG observed in the 3=SL of flaviviruses were absent from strains with the YFVSADM2 deletion.…”
Section: Resultsmentioning
confidence: 96%
“…Although the H67N, A83E, T154A, K177R, and R207K mutations are not considered genetic signatures, they are commonly found in American strains. Furthermore, the K331R mutation was observed in the Brazilian YFV strains and is suggested to be associated with viscerotropism in hamsters (24,25), while the D360E substitution is associated with virulence rescue in attenuated strains (40). The role of other mutations (T120A, A147V, M198R, and T268A) remains uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, direct CNS infection of most YFV strains in mice is lethal (2). This obstacle can be overcome with the use of viscerotropic strains of YFV in hamsters (24,38) or of immunodeficient (e.g., scid) mice with increased sensitivity to YFV by peripheral routes of infection (6). We show in this study that type I and II interferons are crucial in restricting viral replication in the mouse visceral organs, hence adult IFN-␣/␄-R ÏȘ/ÏȘ mice are uniformly FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sequential series of liverto-liver passages of YFVs in hamsters led to the generation of viral strains that cause a more lethal disease in hamsters (21,33,39). Instead of serial passaging, we performed alternate passaging of DEN between mosquito cells and mice to obtain D2S10, thereby approximating the natural transmission cycle of DEN between mosquitoes and humans.…”
Section: Discussionmentioning
confidence: 99%